Cystitis in a Bitch with Chronic Kidney Disease Caused by Multidrug-Resistant Escherichia coli - Yun, Jongchul; Yun, Taesik; Koo, Yoonhoi; Chae, Yeon; Lee, Dohee; Kang, Byeong-Teck; Yang, Mhan-Pyo; Kim, Hakhyun (Acta Scientiae Veterinariae, 2022)
Background: In dogs with bacterial cystitis that is resistant to multiple antibiotics, resulting from repeated infections and antimicrobial administration, especially if the dog has impaired renal function and the induction of systemic side effects by intravenous or oral administration is a concern, intravesical instillation of antibiotics might represent an alternative treatment option. In human and veterinary medicine, a number of studies showed intravesical instillation of antibiotics is effective for the therapy multidrug-resistant bacterial urinary tract infection (UTI). This report firstly illustrates successful intravesical meropenem treatment of a UTI caused by multidrug-resistant Escherichia coli with no systemic side effects in dog with chronic kidney disease (CKD). Case: A 15-year-old spayed female Maltese was presented with recurrent bacterial cystitis. The risk factors for the recurrent UTI were spinal cord injury and CKD which had been managed for 1 year. Ultrasound-guided cystocentesis was performed to obtain a urine sample for urinalysis, bacteriologic culture, and antibiotic susceptibility testing. Bacterial cystitis caused by multidrug-resistant Escherichia coli was diagnosed on the basis of bacterial culture, and antimicrobial susceptibility testing. Because the dog had CKD, reducing the clearance of meropenem, intravesical instillation of antibiotics was initiated. The intravesical instillation process consisted of the emptying of the urinary bladder, infusion of a diluted meropenem solution (8.5 mg/kg diluted in 20 mL of saline solution) into the bladder through a urethral catheter, and retention of the meropenem solution in the bladder for 1 h, and its removal. The procedure was repeated every 8 h. On day 8 of the intravesical instillation therapy, Bactereologic culture yielded a growth of E. coli (50,000 CFUs/mL), which was less than previously obtained. the concentration of the meropenem solution being administered was increased to 17 mg/kg diluted in 20 mL of saline solution, to improve the effectiveness of the therapy. After 21 days of the intravesical meropenem instillation, the bacterial cystitis was resolved. One year after completion of the treatment, the dog is still alive without any recurrence of bacterial cystitis. Discussion: Because resistant uropathogens can cause zoonotic infections, effective therapy is important with increasing incidence not only for patients, but also for public health. Intravesical instillation of antibiotics can be an effective treatment method for dogs with urinary tract infection in which oral antibiotics are likely to be ineffective and injectable antibiotics cannot be a treatment option. The antibiotics can be administered directly to the affected location, and systemic side effects can be minimized by the impermeabtility of the bladder wall via intravesical instillation procedure. Meropenem is likely to accumulate in dogs with impaired renal function, leading to systemic side effects and the aggravation of CKD in old dogs. This report describes the successful treatment of multidrug-resistant E. coli infection by intravesical instillation of meropenem without any side effects in dogs with CKD. Therefore, clinician should consider the use of intravesical instillation of antibiotics which predominately excreted in the urine for the control of urinary tract infection caused by multidrug-resistant bacteria in dogs showing reduced renal function. Keywords: canine, intravesical instillation, meropenem, multidrug-resistant organism, urinary tract infection.